Complementary and alternative medicine in radiation oncology: Survey of patients’ attitudes Komplementär- und Alternativmedizin in der Radioonkologie: Umfrage zur Patientenakzeptanz - Lettner, Sabrina; Kessel, Kerstin A.; Combs, Stephanie E. (Strahlentherapie und Onkologie, 2017)
Background: Complementary and alternative medicine (CAM) are gaining in importance, but objective data are mostly missing. However, in previous trials, methods such as acupuncture showed significant advantages compared to standard therapies. Thus, the aim was to evaluate most frequently used methods, their significance and the general acceptance amongst cancer patients undergoing radiotherapy (RT). Methods: A questionnaire of 18 questions based on the categorical classification released by the National Centre for Complementary and Integrative Health was developed. From April to September 2015, all patients undergoing RT at the Department of Radiation Oncology, Technical University of Munich, completed the survey. Changes in attitude towards CAM were evaluated using the questionnaire after RT during the first follow-up visit (n = 31). Results: Of 634 patients, 333 answered the questionnaire (52.5%). Of all participants, 26.4% used CAM parallel to RT. Before RT, a total of 39.3% had already used complementary medicine. The most frequently applied methods during therapy were vitamins/minerals, food supplements, physiotherapy/manual medicine, and homeopathy. The majority (71.5%) did not use any complementary treatment, mostly stating that CAM was not offered to them (73.5%). The most common reasons for use were to improve the immune system (48%), to reduce side effects (43.8%), and to not miss an opportunity (37.8%). Treatment integrated into the individual therapy concept, e.g. regular acupuncture, would be used by 63.7% of RT patients. Conclusion: In comparison to other studies, usage of CAM parallel to RT in our department is considered to be low. Acceptance amongst patients is present, as treatment integrated into the individual oncology therapy would be used by about two-third of patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cancer; Holistic medicine; Immune system; Radiotherapy; Side effects